Insulin Requirement and Complications Associated With Serum C-Peptide Decline in Patients With Type 1 Diabetes Mellitus During 15 Years After Diagnosis - Suh, Junghwan; Lee, Hae In; Lee, Myeongseob; Song, Kyungchul; Choi, Han Saem; Kwon, Ahreum; Kim, Ho-Seong; Chae, Hyun Wook (Frontiers in Endocrinology, 2022)
Objective C-peptide is conventionally used in assessing pancreatic function in patients with diabetes mellitus. The clinical significance of this molecule during the course of type 1 diabetes mellitus (T1DM) has been recently revisited. This study aimed to investigate the natural course of C-peptide in T1DM patients over the period of 15 years and analyze the association between the residual C-peptide and diabetes complications. Methods This retrospective study included a total of 234 children and adolescents with T1DM. Patient data including sex, age at diagnosis, anthropometric measures, daily insulin dose, serum HbA1c, post-prandial serum C-peptide levels, lipid profiles, and diabetic complications at the time of diagnosis and 1, 3, 5, 10, and 15 years after diagnosis were retrospectively collected. Results Among the 234 patients, 101 were men and 133 were women, and the mean patient age at initial diagnosis was 8.3 years. Serum C-peptide decreased constantly since the initial diagnosis, and showed a significant decline at 3 years after diagnosis. At 15 years after diagnosis, only 26.2% of patients had detectable serum C-peptide levels. The subgroup with older patients and patients with higher BMI standard deviation score showed higher mean serum C-peptide, but the group-by-time results were not significant, respectively. Patients with higher serum C-peptide required lower doses of insulin and had fewer events of diabetic ketoacidosis. Conclusion Serum C-peptide decreased consistently since diagnosis of T1DM, showing a significant decline after 3 years. Patients with residual C-peptide required a lower dose of insulin and had a lower risk for diabetic ketoacidosis.